Genetic Diversity Of Some Restorer Lines For Hybrid Rice Development - Kulsum, MU; Hasan, MJ; Begum, H; Billah, MM; Rahman, H (Bangladesh Journal of Agricultural Research, 2011)
Genetic divergence of thirty six restorer lines was studied through Mohalanobis’s D2 and principal component analysis for nine characters. Genotypes were grouped into five different clusters. Cluster III comprised of maximum number of genotypes (eleven) followed by cluster I and IV. The inter-cluster distance was maximum between clusters II and IV (14.064) indicating wide genetic diversity between these two clusters followed by the distance between cluster II and V (10.353), cluster III and cluster IV (8.588). The minimum inter- cluster distance was observed between cluster I and cluster III (2.885) followed by cluster I and cluster V (4.359) and cluster III and cluster V (4.825) indicating that the genotypes of these clusters were genetically close. The intra cluster distance in the entire five clusters was less, which indicated that the genotypes within the same cluster were closely related. Among the characters, number of tillers/hill, panicle length, number of filled spikelets/ panicle, spikelet fertility % and yield/plant contributed most for divergence in the studied genotypes. It indicates that these parameters can contribute more for yield in hybrid rice development. Keywords: Rice; restorer line; genetic divergence; D2. DOI: http://dx.doi.org/10.3329/bjar.v36i1.9226 BJAR 2011; 36(1): 21-28